PEKERJAAN SOSIAL DAN FILANTROFI ISLAM Tinjauan Historis Dan Implikasinya Terhadap Perkembangan Ilmu Pekerjaan Sosial - Abdul Najib (Universitas Islam Negeri (UIN) Mataram, 2016)
Social works and philantropi are two thing that have substantive meaning. The development of philantropy has been existed in the classical as well as modern era. In the era of Islamic government, especially Umayyah dynasty, Daulah Abbasiyah, and Turki Usmani philantropy has been arranged variously, and it differs from previous Islamic government: however, substantially they have same form and complementary relationship. At this moment the form of philantropy is the same with the previous era, but it has difference in terms of the management of activities; in which the managerial activities are well-organized. Based on the philantorpic activities during the Islamic golden era, it might have implication to the study of modern social work since it is historically grounded on philantropic activities. Actually, the concept of Islamic philantropy is based on Al-Quran about the essence of human as a servant and God’s servant in the world. Generally, the historical backgrounds of social works in the Western and Islamic context are the same because the notion of social works in the sense of charity derives from either the concept of philantropic church and cultural order. Meanwhile, in earlier era of Islam under the Prophet Muhammad S.AW, the philantropy has been perfectly practiced until now. The difference is the Western people commence to use the concept established based on modern science.